Preventing Child Maltreatment in Low‐ and Middle-Income Countries: Parenting for Lifelong Health in the Philippines - Alampay, Liane Peña (Archīum Ateneo, 2018)
The 2030 Global Agenda for Sustainable Development includes ending all forms of violence against children as an explicit goal (SDG target 16.2). This chapter highlights the scientific basis and potential of parent education and skills development programs to prevent child maltreatment, and describes the Parenting for Lifelong Health (PLH)-Philippines project as an example of such an initiative in a low-resource setting. PLH-Philippines is a local and international multi-sectoral collaboration that conducted a rigorous test of a culturally-adapted parenting intervention, the Masayang Pamilya Para Sa Batang Pilipino (MaPa; Happy Family for the Filipino Child), within the Philippines’ conditional cash transfer service delivery system. The contributions and challenges of Developmental Science in achieving the SDG target of preventing violence against children, particularly via family-focused interventions in low and middle-income contexts, are discussed.